2021
DOI: 10.5041/rmmj.10432
|View full text |Cite
|
Sign up to set email alerts
|

Career Trajectory of Physicians Following a Fellowship Program: A Descriptive Study

Abstract: Introduction. A clinical and/or research fellowship abroad has become a prevalent choice among Israeli physicians. However, the influence of fellowship programs on the career path is unclear. We evaluated the role of physicians returning from fellowship in the organizational hierarchy and their professional and academic status. Methods. This was a retrospective, descriptive, cross-sectional study of physicians who completed a survey after accomplishing a fellowship. The survey included questions about the phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Other professions have also examined career opportunities for other postdoctoral graduates. [31][32][33][34][35] Medical fellowships, dental residencies, pharmacy residencies, and other scientific postdoctoral training programs indicate increased opportunities in research and academic teaching roles. [31][32][33][34][35] More specifically, Berger et al 35 in 2021 performed a crosssectional study of physicians who completed a survey after fellowship training.…”
Section: Weekly Job Dutiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other professions have also examined career opportunities for other postdoctoral graduates. [31][32][33][34][35] Medical fellowships, dental residencies, pharmacy residencies, and other scientific postdoctoral training programs indicate increased opportunities in research and academic teaching roles. [31][32][33][34][35] More specifically, Berger et al 35 in 2021 performed a crosssectional study of physicians who completed a survey after fellowship training.…”
Section: Weekly Job Dutiesmentioning
confidence: 99%
“…[31][32][33][34][35] Medical fellowships, dental residencies, pharmacy residencies, and other scientific postdoctoral training programs indicate increased opportunities in research and academic teaching roles. [31][32][33][34][35] More specifically, Berger et al 35 in 2021 performed a crosssectional study of physicians who completed a survey after fellowship training. Similar to our finding, results from their paper demonstrated that a high number of fellowship-trained physicians more often held "managerial positions, academic appointments, and had generated significant research" in their field.…”
Section: Weekly Job Dutiesmentioning
confidence: 99%